THE CONCEPT OF "CONSTRUCTIONISM" AND THE MAIN ASPECTS OF ITS STUDY. NECESSARY CONDITIONS FOR THE EMERGENCE AND HISTORY OF CONSTRUCTIONISM - Nurmetova Fazilat Ilhomovna (Western European Studies, 2024)
The study of international relations can be transformed by using the substantial and multifaceted significance of social construction in global politics. Fundamentally, social constructivism reveals the primary mechanisms that form the international scene and redirects attention away from simply material explanations, such economic and military prowess, and toward the ideological and social aspects of world politics. This change is essential to comprehending the modern world, in which identity politics, soft power, and international standards all have a growing impact on state behaviour and international outcomes.
Keywords: growing; standards; impact